2022
DOI: 10.3389/fneur.2022.904145
|View full text |Cite
|
Sign up to set email alerts
|

Frontal, Sensorimotor, and Posterior Parietal Regions Are Involved in Dual-Task Walking After Stroke

Abstract: BackgroundWalking within the community requires the ability to walk while simultaneously completing other tasks. After a stroke, completing an additional task while walking is significantly impaired, and it is unclear how the functional activity of the brain may impact this.MethodsTwenty individual in the chronic stage post-stroke participated in this study. Functional near-infrared spectroscopy (fNIRS) was used to measure prefrontal, pre-motor, sensorimotor, and posterior parietal cortices during walking and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…The right PoCG, similar to the right cerebellum VIIIa, was also responsible for somatic sensory functions, which suggested that sensorimotor function might play an important role in the GBD of CSVD patients. In a previous study, stroke patients with sensorimotor deficits were more likely to experience a severe loss of postural control ( Lim et al, 2022 ). In the elderly, overactivation of the sensorimotor network may be indicative of compensatory processes for poor gait performance ( Di Scala et al, 2019 ).…”
Section: Discussionmentioning
confidence: 97%
“…The right PoCG, similar to the right cerebellum VIIIa, was also responsible for somatic sensory functions, which suggested that sensorimotor function might play an important role in the GBD of CSVD patients. In a previous study, stroke patients with sensorimotor deficits were more likely to experience a severe loss of postural control ( Lim et al, 2022 ). In the elderly, overactivation of the sensorimotor network may be indicative of compensatory processes for poor gait performance ( Di Scala et al, 2019 ).…”
Section: Discussionmentioning
confidence: 97%
“…Two of them found that step speed and length were decreased, cortical activation of PFC ( Orcioli-Silva et al, 2021 ) and SMA ( Pelicioni et al, 2022 ) were increased under obstacle negotiation dual-task conditions compared with single task condition. Three of them found step speed was decreased, cortical activation of PFC ( Hawkins et al, 2018 ; Collett et al, 2021 ; Lim et al, 2022a ), SMC ( Lim et al, 2022a ), and PMC ( Lim et al, 2022a ) were increased in stroke patients during walking under dual-task conditions compared with single-task condition ( Collett et al, 2021 ; Lim et al, 2022a ) or compared with healthy older adults ( Hawkins et al, 2018 ). Two studies of MS patients found that step speed was decreased and cortical activation of PFC was increased under dual-task conditions ( Hernandez et al, 2016 ) during walking compared to healthy older adults ( Chaparro et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two articles adopted walking whilst n-back (Hermand et al, 2019 , 2020 ). Two articles adopted walking whilst a verbal task (Hawkins et al, 2018 ; Lim et al, 2022 ). Only one paper adopted walking whilst picture-planning or stroop (Collett et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“… Sensitivity analysis for comparing PFC activation of ST and DT. When the following studies were excluded, the heterogeneity of the combined results was as follows: I 2 = 9.878% (Al-Yahya et al, 2016 ); I 2 = 6.688% (Chatterjee et al, 2019 ); I 2 = 3.832% (Clark et al, 2021 ); I 2 = 5.709% (Hawkins et al, 2018 ); I 2 = 11.319% (Hermand et al, 2019 ); I 2 = 9.19% (Hermand et al, 2020 ); I 2 = 0% (Collett et al, 2021 ); I 2 = 9.03% (Lim et al, 2022 ); I 2 = 11.411% (Mori et al, 2018 ). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation